2012
DOI: 10.1021/jp211863y
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Colloids and Activation Agents for Determination of Melamine Using UV-SERS

Abstract: UV-SERS measurements offer a great potential for environmental or food (detection of food contaminats) analytics. Here, the UV-SERS enhancement potential of various kinds of metal colloids, such as Pd, Pt, Au, Ag, Au–Ag core–shell, and Ag–Au core–shell with different shapes and sizes, were studied using melamine as a test molecule. The influence of different activation (KF, KCl, KBr, K2SO4) agents onto the SERS activity of the nanomaterials was investigated, showing that the combination of a particular nanopar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 41 publications
0
20
1
Order By: Relevance
“…[151,152] Other UV appropriate metals such as platinum and rhodium do not oxidize, but they are rare in abundance and deemed impractical for device design. [153][154][155] Aluminum (Al) on the other hand has received the most attention following the pioneering work by Knight et al in which they demonstrated plasmonic resonance of single Al nanorods, imaged at wavelengths from 248 to 539 nm, showing both UV and visible resonance for transverse and longitudinal modes. [156] Al is a promising candidate for UV plasmonics considering its natural abundance and low cost, UV resonance range down to 210 nm, and a self-limiting native oxide which is typically only 2-3 nm thick.…”
Section: Perspective On New Materials For Broader Wavelength Rangementioning
confidence: 99%
“…[151,152] Other UV appropriate metals such as platinum and rhodium do not oxidize, but they are rare in abundance and deemed impractical for device design. [153][154][155] Aluminum (Al) on the other hand has received the most attention following the pioneering work by Knight et al in which they demonstrated plasmonic resonance of single Al nanorods, imaged at wavelengths from 248 to 539 nm, showing both UV and visible resonance for transverse and longitudinal modes. [156] Al is a promising candidate for UV plasmonics considering its natural abundance and low cost, UV resonance range down to 210 nm, and a self-limiting native oxide which is typically only 2-3 nm thick.…”
Section: Perspective On New Materials For Broader Wavelength Rangementioning
confidence: 99%
“…For the case of 532 nm excitation laser, silver nanostructures have a smaller photothermal effect than gold ones, leading to a larger enhancement factor [ 35 , 38 ]. Besides silver, other materials such as aluminum, lead, and platinum are also good choices, but silver could be the best choice with a much easier fabrication process [ 39 , 40 , 41 , 42 ]. A detection limit down to 10 −16 M for Rhodamine 6G has been reported by silver metasurfaces formatted with nanobowties [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the presence of melamine, hydrogen peroxide will react with melamine to produce a stable addition compound. 18 With the consumption of hydrogen peroxide, the growth of Au NPs will be slow down, resulting Au NPs aggregations to give a blue solution, which is illustrated by Scheme 1. There is no need to prepare functionalized gold nanoparticles at all.…”
Section: Introductionmentioning
confidence: 99%